Sifat Fisik Kacang Tanah Pada Varietas Talam 1, Varietas Talam 2 Dan Varietas Takar 2 - Isnaini Puspitasari; Sandra Sandra; Yusuf Wibisono (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2019)
The physical properties of agricultural products are very important for designing tools and machines for processing products. The quality of peanuts is determined by physical properties. The physical properties that determine the quality of peanuts are the air content and physical quality of seeds (whole seeds, wrinkled seeds, and damaged seeds). The physical properties of peanuts must be considered the size of peanuts (area and volume), true density, bulk density, porosity, angle of friction used for drying and storage. On Measuring the Physical Properties of Peanuts Various Types of Variations Each of which Has Different Values. In the measurement of the average large dimension value of the Talam 2 variety has a number of 14.48 ± 0.97, the average width value required by Takar 2 and Talam 1 varieties is 8.55 ± 0.57 and. Measure 2 has an arithmetic mean diameter value, geometric mean diameter, surface area, and overall volume as a whole - 9.9 ± 0.56, 9.62 ± 0.36, 291.05 ± 22.07, 468 , 03 ± 52.59. This happens because the Takar 2 variety peanut has a larger seed shape and more containing seeds. Glass is a friction surface that has the highest coefficient of static friction.